2014
DOI: 10.14295/transportes.v22i2.730
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de apoio à decisão para um problema de posicionamento de bases, alocação e realocação de ambulâncias em centros urbanos: estudo de caso no município de São Paulo

Abstract: INTRODUÇÃOO serviço de atendimento de urgência, ou emergência, compreende os primeiros socorros e a remoção de pacientes sujeitos a acidentes, traumas e outras ocorrências médicas que podem representar risco a vidas humanas. Buscase oferecer um serviço que maximize a probabilidade de sobrevivência dos socorridos, desde o acontecimento da situação de risco até a entrada do paciente em uma unidade de saúde especializada. Todo o trabalho é realizado por veículos de transporte e suporte à vida.As chances de sobrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Since then, various systems have been applied. Some examples of hypercube applications are power distribution outage analysis in Santa Catarina (Albino, 1994), police patrolling, firefighting (Costa, 2004), highway patrol service (Geroliminis et al., 2009), mobile city bus repair system (Geroliminis et al., 2011), emergency medical systems on highways (Mendonça and Morabito, 2000; Iannoni and Morabito, 2006; Iannoni et al., 2008; Chiyoshi et al., 2011), emergency medical systems in urban areas (Takeda et al., 2004; Souza et al., 2013; Andrade and Cunha, 2014; Kim and Lee, 2015; Ghussn and Souza, 2016), emergency maintenance service system in the sugarcane industry (Rodrigues et al., 2018), among others.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Since then, various systems have been applied. Some examples of hypercube applications are power distribution outage analysis in Santa Catarina (Albino, 1994), police patrolling, firefighting (Costa, 2004), highway patrol service (Geroliminis et al., 2009), mobile city bus repair system (Geroliminis et al., 2011), emergency medical systems on highways (Mendonça and Morabito, 2000; Iannoni and Morabito, 2006; Iannoni et al., 2008; Chiyoshi et al., 2011), emergency medical systems in urban areas (Takeda et al., 2004; Souza et al., 2013; Andrade and Cunha, 2014; Kim and Lee, 2015; Ghussn and Souza, 2016), emergency maintenance service system in the sugarcane industry (Rodrigues et al., 2018), among others.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The main goal is to provide a solution to reach all users at a maximum acceptable time or distance, defined as the critical value. Some recent studies for SAMU can be found by [14], [2], [19] and [9].…”
Section: Related Workmentioning
confidence: 99%